(untitled) - Flores, Fernanda; Parra, Viviana Gladys; Cacciavillani, Julio; Innocenti, Carolina (Universidad Nacional de Cuyo. Facultad de Ciencias Médicas)

¿Cuál es su diagnóstico? (2009)

(untitled)
Fil: Flores, Fernanda. Hospital Luis Lagomaggiore (Mendoza, Argentina). Servicio de Dermatología